The Impact of Live Streaming and Flash Sale on Gen Z Purchase Intention in Shopee - Nazma Mega Prameswari; Neng Keke Nuraeni; Nur Hayati - (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the effect of live streaming and flash sales at the Shopee marketplace on the buying interest of Gen Z consumers in Bandung City, platforms such as Shopee, which allow consumers to shop anywhere and anytime. With the ease of accessing various online shopping platforms, many companies are trying to attract consumer attention through multiple strategies, one of which is live streaming and flash sales. This research was designed using quantitative methods, focusing on the population of Shopee Generation Z users in Bandung City. The method used is non-probability sampling with a purposive sampling technique; the sample size is 121 respondents with reference to Roscoe's theory. The results of this study indicate that live streaming partially increases Gen Z's buying interest in Bandung City, flash sales increase Gen Z's purchase interest in Bandung positively partially, and live streaming and flash sales simultaneously have a significant effect on Gen Z's buying interest in Bandung City.